2011
DOI: 10.1007/s10620-011-1814-8
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and the Association of Advanced Colorectal Neoplasia in an Asymptomatic Average Risk Population: Analysis of Exposure and Anatomical Location in Men and Women

Abstract: Women smokers had an increased risk for advanced adenomas at a lower exposure level and had a greater risk for proximal lesions. These findings may have an impact on CRC screening for women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 42 publications
(57 reference statements)
3
13
0
Order By: Relevance
“…Furthermore, the 50% prevalence of adults in the NHCR who had a smoking exposure, past or current, has also been observed in other similar screening populations 11 . Therefore, while adjustment for smoking or obesity may be needed in a population with a particularly high prevalence of these risk factors, especially if many individuals have a 20 pack year or greater exposure, stratification may not be necessary in typical screening populations.…”
Section: Discussionsupporting
confidence: 60%
“…Furthermore, the 50% prevalence of adults in the NHCR who had a smoking exposure, past or current, has also been observed in other similar screening populations 11 . Therefore, while adjustment for smoking or obesity may be needed in a population with a particularly high prevalence of these risk factors, especially if many individuals have a 20 pack year or greater exposure, stratification may not be necessary in typical screening populations.…”
Section: Discussionsupporting
confidence: 60%
“…In addition, we showed in a large screening cohort with an almost equal distribution of men and women that the association was significantly stronger for women. A study on 1996 individuals investigated the impact of exposure level of smoking, and revealed that female smokers had an increase risk for advanced adenomas compared with non-smokers at a lower exposure level than man (Anderson et al , 2011). Exposure levels were not assed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with their non-smoker peers, women smokers are at significantly greater risk of advanced colorectal neoplasia after as little as 10 pack-years of smoking, whereas for men it takes 30 or more pack-years for the risk to reach statistical significance [13]. Previous studies revealed a gender difference in the effect of smoking on bladder cancer risk; however, one recent study following approximately 500,000 participants reported that smokers, regardless of gender, were at a 50 % higher risk for developing bladder cancer compared with never smokers [14].…”
Section: Smoking and Cancermentioning
confidence: 99%